2018
DOI: 10.5114/jos.2018.80643
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effectiveness of virgin coconut oil mousse against Candida albicans biofilm in children with early childhood caries

Abstract: Introduction: Early childhood caries is defined as the presence of one or more decayed teeth, missing (due to caries) or filled teeth surface in a child 71 months of age or younger. The presence of Candida albicans will increase caries pathogenicity. Objectives: The objective of this study was to analyze the antifungal effectiveness of virgin coconut oil (VCO) mousse against viability of C. albicans biofilm in children with early childhood caries. Material and methods: In this experimental laboratory study, C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The systemic treatment was kept same in both the groups as only the topical agents were being compared. A progressive decrease in the score for itch from baseline score to 12 th week of treatment in the present study was similar to that reported by Monica et al 12 in their study. Improvements were seen in erythema, scaling, papules, and vesicula" on and peripherally ac" ve margin in the present study, with topical clotrimazole usage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The systemic treatment was kept same in both the groups as only the topical agents were being compared. A progressive decrease in the score for itch from baseline score to 12 th week of treatment in the present study was similar to that reported by Monica et al 12 in their study. Improvements were seen in erythema, scaling, papules, and vesicula" on and peripherally ac" ve margin in the present study, with topical clotrimazole usage.…”
Section: Discussionsupporting
confidence: 93%
“…The total study period encompassed 12 weeks. Mycological diagnosis by KOH mount was performed at baseline and repeated at each subsequent visit i.e., 4,8,12 weeks. All the study pa!…”
Section: Methodsmentioning
confidence: 99%